Lobo em pele de cordeiro : do discurso Iurdiano aos danos causados aos seus seguidores - Cunha, Eduardo Pessoa Crucho (2016)
The debate in the religious field has always been successful in building possibilities of understanding of society, in its forms of sociability established to interpret and / or reflect the prospect of an era. In Brazilian contemporary formulation of these dimensions we have combined the entry of new actors and social institutions. In the case of this specific work, the Universal Church of the Kingdom of God (UCKG) has as its most representative founder Bishop Macedo, who since the 1970s has been building and expanding the spaces in the Brazilian religious life. Gift of various media, ta king its greatest Record brand, one sees a speech that is embodied by the significant increase in believers. However, what we show in this paper is not the perspective of the expanding Church, we analyze the church speech and its implications for ethical and legal nature of the damage caused to the faithful who have not had their promises fulfilled in the marketing logic graces due rites and practices dictated by the UCKG. Besides the legal issues contextualize the social context that is inserted speeches, damage, but mainly its logical action. This implies not only deal with the marketing aspect of the faith, but to include this practice in a society model based on consumerist values which the most fundamental values are lost due to the most basic needs and, above all, respect for moral ethical principles that guide human dignity.